The Softbag - Rainer Pirker (Oz, 2003)
Think of a travel bag in contrast to a suitcase! Hard bags are predefined in their shape. Their structure is determined by the stiffness of the shell. Filling hard bags, room has to be found for each piece. The predefined shell reduces the possibilities.